The practice of hegemony by lecturers of a public university in virtual classrooms/ Nor Asni Syahriza Abu Hassan ... [et al.] - Abu Hassan, Nor Asni Syahriza; Amat, Rafidah; Saad, Sharina; Mansor, Nur Syazwanie; Abd Rahim, Mas Aida (Universiti Teknologi MARA, Perak, 2024)
The ability to control or influence others to follow instructions demonstrates hegemony, or power. In the context of education, the success of teaching and learning often hinges on the power the educators hold in the classroom. However, teaching methods must adapt to varying circumstances. In the era of technology, virtual-teaching platforms have supplanted traditional in-person classroom interactions. This paper aims to explore the challenges lecturers face during virtual classrooms and their strategies in asserting power to address these challenges. The study surveyed lecturers from UiTM Kedah using a questionnaire to gain insight into their experiences and strategies. The results indicated that respondents effectively utilized different bases of power to navigate the challenges of virtual classrooms. The findings also suggest that demonstrating power in a virtual classroom requires diverse and adaptable approaches to ensure the success of the teaching and learning process, ultimately benefiting all students.